PENGARUH GOOD CORPORATE GOVERNANCEDAN LAVERAGE TERHADAP KINERJA KEUANGAN PERUSAHAAN PERBANKAN YANG TERDAFTAR DIBURSA EFEK INDONESIA (BEI) Periode 2016-2020 - Sulisti Indriyani; Andria Referli; Alean Kistiani Hegy Suryana (Universitas Boyolali, 2021)
This study aims to determine the effect of the audit committee, institutional ownership, independent commissioners, leverage on the financial performance of banking companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. This study uses a descriptive approach to determine the value of the independent variable, either one or more (independent) variables without making comparisons, or connecting with other variables. The data collection technique was carried out by collecting data using the literature study method. Secondary data in this study can be obtained by accessing the website www.idx.co.id. The data analysis technique used quantitative techniques with a statistical approach, namely the classical assumption test consisting of normality test, multicollinearity test, heteroscedasticity test and autocorrelation test, as well as multiple linear regression analysis. The audit committee, institutional ownership, board of commissioners and leverage have low partial effect (t-test) on financial performance (ROA). Based on the F test, it can be seen that GCG and Laverage with a value of 0.106 are smaller than 0.05, which means that they simultaneously have low effect on Financial Performance.